THE ENGLISH SPEAKING ANXIETY OF NURSING SCIENCE STUDENTS OF STIK BINA HUSADA PALEMBANG - Agus Wahyudi (Language and Education Journal, 2016)
Learning a foreign language is closely related to human psychology, where learners sometimes got anxiety which is the common reaction in English classes. Horwitz (2001) states that one-third of the students who study foreign languages experience at least at an average level. The population of this study was the nursing science students of STIK Bina Husada in the 2016/2017 academic year; the sample of this study was the second-semester students who took English II subject, where there were 45 students consisting of 15 males and 30 females. The purposes of this research were to find out the frequency and the level of English speaking anxiety of Nursing Science Students STIK Bina Husada Palembang. The frequency of English speaking anxiety was categorized into very often, often, seldom, and never, while the level of English speaking anxiety was categorized into high, moderate, and low. To collect the data, two questionnaires of an English speaking anxiety adapted from Horwitz, Horwitz, and Cope (1986) were distributed. The result of this study showed that 6 students (13%) answered very often, 18 students (40%) answered often, 19 students (42%) answered seldom, and 2 students (5%) answered never felt anxious when speaking English in the class. Further, the second questionnaire showed that 2 students (5%) were in the high category, 42 students (93%) were in moderate, 1 student (2%) was in low anxiety. In accordance with the students’ answers, it was hoped that the students realized that it was natural to make mistake in English class.